Prediction of the drying behavior of debris in Fukushima Daiichi Nuclear Power Station for dry storage. Issue 10 (3rd October 2018) - Nakayoshi, Akira; Suzuki, Seiya; Okamura, Nobuo; Watanabe, Masayuki; Koizumi, Kenji
ABSTRACT: Although treatment policies for debris from Fukushima Daiichi Nuclear Power Station have not been decided yet, they may include medium-and long-term debris storage. Dry storage may be desirable in terms of cost and handling, but before implementation, it is necessary to assess hydrogen generation that occurs during storage due to the radiolysis of the water accompanying the debris. Herein, Al2 O3, SiO2, ZrO2, UO2, and cement paste pellets were prepared as simulated debris with various porosities and pore size distributions. The weight changes of the wet samples were measured at various drying temperatures (100°C, 200°C, 300°C, and 1000°C) via thermogravimetry under helium gas flow (50 cc/min) or reduced pressure conditions (rate: 200 Pa in 30 min), and the resulting drying curves were evaluated. All ceramic pellets exhibited similar drying characteristics in this experiment, indicating that cold ceramics could be used for predicting the drying behavior of ceramic debris. In compariosn with ceramic pellets, cement paste pellets exhibited different behavior and a longer drying time even under 1000°C. In conclusion, it is necessary to decide a standard level for the dry state of molten core concrete interaction (MCCI) products that accompany concrete.